Guerilla Marketing: Pengaruh Guerilla Advertising terhadap Awareness dan Image Produk bagi Perusahaan - Pratama, Ady Putra (Jurnal Aplikasi Manajemen, 2016)
Advertising is the part of the promotion. In Indonesia, many companies use promotionsÂ in order to increase sales. Advertising sends the message and brand value to theÂ consumers. The amount of advertising that is conventionally leading to saturation forÂ consumers in Indonesia. The concept of guerilla advertising is one of the advertising conceptsthat are creative and attractive advertising in affecting consumers'awareness. CompaniesÂ can use the concept of guerilla advertising as a new concept that is easy to implementÂ and use low budgets. Guerilla advertising has a positive and negatif effect for the company.Â The use of guerilla advertising technique itself is deemed to be less credible due to languageÂ and delivery using an extreme way. However, guerilla advertising is very importantÂ because it is used by a company beside it is issued a small budget, geruilla advertisingÂ concept is a new concept and can affect consumers' awareness with an easy and innovativeÂ way.